The Role of School Management in Supporting The Implementation of The Merdeka Curriculum in Indonesian Schools in Johor Bahru, Malaysia - Rudiatwoko, Sigit; Karwanto; Mustaji; Amrozi Khamidi; Mochamad Nursalim (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
The study aims to examine the role of school management in supporting the implementation of the "Kurikulum Merdeka" (Freedom Curriculum) in Indonesian schools abroad, specifically at Sekolah Indonesia Johor Bahru (SIJB), Malaysia. As an educational reform, Kurikulum Merdeka aims to foster students’ development aligned with Pancasila values through flexible, student-centered learning methods. Using a qualitative method involving interviews, observations, and document analysis, the study analyzes the planning, organizing, implementation, and evaluation processes of the curriculum at SIJB. Findings indicate that effective school management significantly supports the curriculum’s implementation by addressing challenges and optimizing the educational environment, helping shape students in line with Pancasila’s characteristics.